2009
DOI: 10.1021/la802769m
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Bacterial Pathogens by Carbon Nanotubes in Suspensions

Abstract: In the study, we explored the antimicrobial activities of single-walled carbon nanotubes (SWNTs) and multiwalled carbon nanotubes (MWNTs) with different surface groups to bacterial pathogens, including Gram-negative vs Gram-positive species and rod-shaped vs round-shaped species. We report here for the first time that SWNTs' antimicrobial activity is buffer and concentration dependent, and the charge effect of functional groups on the surface of carbon nanotubes (CNTs) is not a critical factor. SWNTs with surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
225
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(256 citation statements)
references
References 50 publications
20
225
1
1
Order By: Relevance
“…These results are in accordance with those of Arias and Yang, and Liu et al, although those experiments were conducted differently and substrates were formulated differently. 59,60 The same observation was reported by Dong et al where single-walled carbon nanotube (SWCNT) tests indicated that the nanotube concentration is the deciding factor for an antibacterial effect. 61 Our results showed that increasing the MWCNT concentration (from 10 to 100 µg mL -1 ) led to increases in the bactericidal effect against E. coli and S. aureus, and these results are very similar to those observed in a study by Liu et al, which reported that the death rate of E. coli increased with an increase in SWCNT concentration from 5 to 80 µg mL…”
Section: Bactericidal Propertiessupporting
confidence: 66%
“…These results are in accordance with those of Arias and Yang, and Liu et al, although those experiments were conducted differently and substrates were formulated differently. 59,60 The same observation was reported by Dong et al where single-walled carbon nanotube (SWCNT) tests indicated that the nanotube concentration is the deciding factor for an antibacterial effect. 61 Our results showed that increasing the MWCNT concentration (from 10 to 100 µg mL -1 ) led to increases in the bactericidal effect against E. coli and S. aureus, and these results are very similar to those observed in a study by Liu et al, which reported that the death rate of E. coli increased with an increase in SWCNT concentration from 5 to 80 µg mL…”
Section: Bactericidal Propertiessupporting
confidence: 66%
“…Heteroaggregation between NPs and cells occur rapidly [110,120,126], and heteroaggregates may continue to grow over time if conditions are favorable [126]. Heteroaggregation may be due to weak physical interactions via DLVO and non-DLVO forces [114] as disaggregation (desorption) has been reported in aqueous conditions that may not affect strong chemical bonds.…”
Section: Heteroaggregation Between Nanoparticles and Microorganismsmentioning
confidence: 99%
“…15,26 Specifically, single-walled CNTs (SWNTs) show the strongest antimicrobial activity. [31][32][33][34] Liao et al 35 reported a concentration-dependent toxicity of GO and graphene in human erythrocytes and skin fibroblasts. Involvement of the reactive oxygen species (ROS) generated by graphene was proposed as one of the main mechanisms for the cytotoxicity of graphene at high concentrations (100 mg/mL) in neural pheochromocytoma-derived PC12, 36 and the size of GO sheets has an effect on the toxicity of GO of high concentration, ie, larger sheets have better biocompatibility in A549 cells.…”
Section: Introductionmentioning
confidence: 99%